Persuasive Communication Of The Igitacy Instagram Account In Promoting Beauty Products - Cindy Meiyori; Sapta Sari; Bayu Risdiyanto (Utami Publisher, 2026)
This study aims to describe the persuasive communication strategies used by the Instagram account @Igitacy in promoting beauty products. The background of this research is based on the growing role of social media, particularly Instagram, as a promotional medium for cosmetic products that relies on personal closeness and influencer credibility. This research employed a descriptive qualitative approach, with data collected through in-depth interviews with the account owner and audience, content observation, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, referring to Lasswell’s communication model. The results show that the account’s credibility is built through consistent posting, high-quality visuals, genuine product use, transparency of information, and intensive interaction with the audience. The message content is structured by introducing the product, explaining its benefits and ingredients, and inviting the audience to try it, using a casual yet informative communication style. The main channels used are Reels and Stories, considered effective for reaching the audience and fostering interaction. The primary target audience is women with similar skin concerns, although the content is designed to remain relevant to a diverse audience. The effects of persuasive communication are reflected in increased interaction, follower growth, and audience trust in the product recommendations provided. This study concludes that the success of @Igitacy’s persuasive communication is influenced by the combination of credibility, structured message design, appropriate channel selection, and the ability to understand the audience. These findings may serve as a reference for marketers and influencers in designing effective promotional strategies on social media.